Obsessive compulsive personality disorder in Progressive Supranuclear Palsy, Multiple System Atrophy and Essential Tremor. (September 2016) - Nicoletti, A.; Luca, A.; Luca, M.; Donzuso, G.; Mostile, G.; Raciti, L.; Contrafatto, D.; Dibilio, V.; Sciacca, G.; Cicero, C.E.; Vasta, R.; Petralia, A.; et al.
Abstract: Introduction: aim of the study was to evaluate the presence of the Obsessive Compulsive Personality Disorder (OCPeD) in Multiple System Atrophy (MSA), Progressive Supranuclear Palsy (PSP) and Essential Tremor (ET) and in a group of healthy subjects. Methods: patients affected by MSA, PSP and ET diagnosed according to currently accepted diagnostic criteria and a group of healthy controls were enrolled in the study. Patients with cognitive impairment were excluded from the study. The Structured Clinical Interview for Personality Disorders-II (SCID-II) has been performed to evaluate the presence of personality disorders (PeDs). The diagnosis of OCPeD was confirmed by a psychiatric interview. Results: fifteen MSA patients (8 men and 7 women; aged 62.9 ± 7.6 years), 14 PSP patients (8 men and 6 women; aged 69.8 ± 4.4 years), 16 ET patients (10 men and 6 women; aged 70.4 ± 6.4 years) and 20 healthy subjects (10 men and 10 women; aged 65.5 ± 6.0 years) were enrolled. OCPeD was recorded in 5 (35.7%) PSP patients, 2 (13.3%) MSA patients, 2 (12.5%) ET patient and 2 (10%) controls. Conclusion: a low frequency of OCPeD, close to those recorded in healthy subjects, was recorded in both MSA and ET patients. Conversely an higher frequency of OCPeD, similar to PD was found among PSP patients, supporting the possibility of an impairment of common basal ganglia network possibly involving the orbito-frontal circuits. Highlights: We evaluated OCPeD in MSA, PSP and ET patients. Fifteen MSA, 14 PSP, 16 ET patients and 20 controls were evaluated through the SCID-II. A low frequency of OCPeD was recorded in MSA, ET patients and controls. A high frequency of OCPeD was found among PSP patients. Our data may be due to an impairment of networks involving the orbitofrontal circuits.